Ultrastructure and Cell Wall Thickness Modification and Its Detection After Chemical Treatments in Huanglongbing Infected Citrus Plants - Shokrollah, Hajivand; Abdullah, Thohirah Lee; Sijam, Kamaruzaman (IntechOpen, 2012)
None